ANALISIS PENGARUH PERGERAKAN BURSA INTERNASIONAL TERHADAP PERGERAKAN BURSA INDONESIA - Johan Halim; Marcories Marcories (Bina Nusantara University, 2011)
The purpose of this study was to determine and obtain empirical evidence on whether there is influence and reciprocal relationships on the movement of international exchanges (Dow Jones, FTSE, Nikkei, Straits Times and Hang Seng), economic conditions, and the relationship between the state of the market movements Indonesia (JSX and IDX). Method of multiple linear regressions with Eviews 5.1 program used in this study to determine the effect of the variables mentioned above. The sample in this study includes daily data for the JSX ongoing since January 1, 2006 through December 31, 2008, and taken to IDX data starting from January 1, 2009 through June 30, 2009. Results of this study are contained influences of the international exchanges separately. No effect occurs when tested simultaneously. JSX influenced by outside markets, but otherwise IDX positively affect international markets. IDX was due to the influence of the shifting influence of the American economy, which affected Subprime Mortgage crisis and the market is already pretty saturated, to Asia which is devoted to research in Indonesia, which is not affected by the Subprime Mortgage and developing countries (developing countries) that could affect other markets Subprime Mortgage crisis affected.Conclusion that there was a shift in which the effect of Indonesia's market affect other markets in the same region even European markets (FTSE) and the U.S. (Dow Jones) due to the improvement in the economic situation of Indonesia that resilience to the global crisis.